(untitled) (Singaporean Journal of Business Economics and Management, 2014)
ABSTRACT This paper aims to investigate the strategies for financing new market innovation by Knowledge-Intensive Business Services (KIBS) firms for socio-economic advancement in Nigeria. A framework is built in which small firms finance new market innovations through utilizing finance from two distinct institutional sources, which are formal (e.g. banks) and informal (e.g. cooperatives etc.) institutions. Primary data through a survey of 510 small and medium sized enterprises (SMEs) inknowledge-intensive businesssector of Lagos, Nigeria at firm level is employed. The findings suggest that the informal sources accommodate the needs of small firms in a developing economy and serve as the primary source of finance for new market innovation. Thus, the informal system should be acknowledged as an integral part of the institutional system influencing innovation in emerging economies. The scope of the study is restricted to only KIBS SMEs in one local context, Lagos, Nigeria. The findings could assist in formulating policy frameworks for supporting innovation, based on utilization of external financial resources by KIBS SMEs in Nigeria. This paper contributes to the literature on financing market innovation and the institutional theory of entrepreneurship in emerging countries, by providing a better understanding of the strategies of the formal and informal institutional sources of finance that are connected with new market innovation by KIBS SMEs in emerging economies.